Acinetobacter baumannii virulence is enhanced by the combined presence of virulence factors genes phospholipase C (plcN) and elastase (lasB). (September 2017) - Kareem, Sawsan Mohammed; Al-Kadmy, Israa M.S.; Al-Kaabi, Marwah Hasan; Aziz, Sarah Naji; Ahmad, Mohammad
Abstract: The ability of multidrug resistance Acinetobacter baumannii to persist in any circumstances regard to the acquisition of many virulence factors genes and antibiotic resistance genes is major concern in the hospitals environments. In this study, thirty A. baumannii isolates were collected from blood infections from hospitalized patients were subjected to screening for virulence factors genes plcN and lasB by conventional PCR. The pathogenicity of representative isolates bearing these gene were tested using galleria mellonella infection assay and adhesion-invasion assay on A549 cell line, and compared with other strain without this gene. Phylogenetic tree revealed that isolates were sorted in two major groups one of them contained two clusters (Group II and III), and another had the other group (Group I). All the 30 A. baumannii isolates were investigated for the presence of virulence factors genes ( plc-N and lasB genes) and results showed that, 16 (53.33%) were harboring lasB genes while 7 (23.3%) isolates were harboring plcN gene The presence of any of these gene enhance the killing ability of A. baumannii strain and increased invasiveness in A549 cell line. Increase nosocomial infection with A. baumannii isolates is serious problem especially because of its potency to gain virulence factors genes and its ability to persist in hospital environments. So the shed light in finding which virulence factors these isolates which have is necessary to discover new antimicrobials that targeting the virulence factor of these powerful pathogens. Highlights: Phylogenetic tree revealed that isolates were sorted into two major groups. Results showed that 16 (53.33%) were harboring lasB genes while 7 (23.3%) isolates were harboring plcN gene. The presence of this gene enhances the killing ability of A. baumannii and increased invasiveness in A549 cell line.